The Relationship Between Private Corporations and the Government: The Importance of a Detailed and Rigorous Public Policy - Iswara, Gregorius Ken Mahisa; Mustofa, Mustabsyirotul Ummah (Candidate: Jurnal Sains Politik, 2025)
Public policy is the most common and effective method for a state to govern its people. Logically, a policy should be clear and detailed so that there is no room for misinterpretation and abuse of power. Unfortunately, many public policies in Indonesia are still unclear and have an impact on society, especially for private corporations. In fact, corporations play an important role in the country's economic growth and through public policy with regards to political economy, regulation, and social aspects. This study aims to explains the relevance of a clear public policy and the consequences that will arise coupled with the challenges that will be faced. The object of research is the government as a policy maker and private corporations. The goal is for the public to understand the urgency of a detailed policy, or at least a derivative policy for corporations to run. The research method used is descriptive qualitative using literature study. There are several findings related to why public policies for corporations can be unclear such as government political will, lobbying, conflict of interest, lack of inclusiveness, and international pressure. In the end, a good policy is one that provides the most benefits for all parties, and such a good policy will not be realized if the government does not have the commitment to implement it.